PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOPERATIF - Fitriani Fitriani; Wiwik Novitasari (Universitas Islam Sumatera Utara, 2017)
Communication skills focus on the importance of speaking, writing, describing and explaining mathematical concepts. In achieving that success is by using cooperative learning model. This model is an effective teaching strategy in improving student achievement and socialization while contributed to their changing of attitudes and perceptions of the importance of learning and cooperation, including for their understanding of their peers from different ethnic backgrounds. This research was conducted at SD IT Faza Azkia Kelurahan Hutaraja, South Tapanuli Regency, North Sumatera Province. This research uses quasi experimental research method. This study aims to describe how to improve students 'mathematical communication skills before and after using cooperative learning model, and also to know the effectiveness of using cooperative learning model in improving students' mathematical communication ability. Based on the results of the study concluded there is an increase in the mathematical communication skills of students before and after using cooperative learning model. And the cooperative learning model is effective for teaching count number operations. This is shown by: the effectiveness of student learning activities, the ability of teachers in managing learning is effective, students 'responses to learning is positive and mastery of students' mathematical communication skills reach 100%.